Assessment of the Influence of Adiponectin, Nesfatin-1, Insulin Resistance, and Various Biochemical Parameters in Samples of Iraqi Individuals Diagnosed with Type 2 Diabetes Mellitus and Pre-diabetes - Raeef, Abdullah Abdulsattar; Mohammed, Mohammed Hashim; Abdullah, Jwan Najm (HAYATI Journal of Biosciences, 2025)
Pre-diabetes is characterized by elevated blood sugar levels that are not yet high enough for a Type 2 diabetes diagnosis. Type 2 diabetes results from insufficient insulin production or cellular resistance to insulin. Adiponectin, secreted by adipose tissue, regulates glucose metabolism and energy balance, while nesfatin-1, derived from NUCB2, influences appetite and energy homeostasis. This case-control study at Al-Ramadi Teaching Hospital included 80 participants with diabetes mellitus (DM) or early-stage DM and 40 healthy controls. Demographic data, including age, Body mass index (BMI), and disease duration, were collected. Laboratory tests measured fasting blood glucose (FBG), Glycated hemoglobin (HbA1c%), insulin, adiponectin, and nesfatin-1 levels. Statistical analyses, including ANOVA, Pearson’s correlation, and AUC analysis, assessed relationships and diagnostic accuracy. Results showed significantly higher levels of FBG, HbA1c, insulin resistance, and nesfatin-1 in early diabetes and DM type 2 cases compared to healthy controls. Nesfatin-1 concentrations were also notably higher in early diabetes compared to other groups. Adiponectin levels did not significantly differ between early diabetes and the control group but were significantly higher in the DM type 2 group. Both early diabetes and DM type 2 were associated with increased FBG, HbA1c, nesfatin-1, and insulin resistance, while adiponectin levels rose only in DM type 2. These findings suggest adiponectin as a potential biomarker for DM type 2, while nesfatin-1 may aid early diabetes diagnosis.